Development of the methods of conducting the developing game "QUIZ" for informal education of schoolchildren of middle and senior classes - Makarenko, Alina (ScienceRise: Pedagogical Education, 2017)
Intellectual games are a good tool in teaching schoolchildren. Since they allow not only to submit new information in an interesting form, which draws the attention of schoolchildren, it is also used to verify the knowledge that has already been obtained. Various intellectual games are used in various spheres and at different levels of training, in this study the application of the intellectual game "QUIZ" in the framework of informal education of schoolchildren of middle and senior classes is considered. The aim of the work is development of a new methodology for conducting intellectual games, which will attract the attention of schoolchildren to various aspects of knowledge, as well as diversify the learning process. In this study, the methodology for conducting the intellectual game QUIZ is developed, various contests that are included in this game, and the methodology for their conduct are described. Studies of the use of this methodology in practice with the use of developed competitions and media materials are conducted. The advantages and disadvantages of using this training method are analyzed. A survey of schoolchildren is conducted, which revealed the success of this training method